La oralidad en la justicia civil como elemento del debido proceso: un enfoque de derechos humanos (2010)
The article proposes the hypothesis that orality is a central element of due process in civil justice; which is derived from the right to a hearing contained in Article 8.1 of the American Convention on Human Rights. This hypothesis is based on four arguments: a) the need to ensure the principle of immediacy in the civil process; b) recognition of the right of hearing as part of due process in other international human rights instruments; c) some pronouncements from agencies and institutions of international and inter-American human rights; and d) the differences between Spanish and English text of Article 8.1 of the American Convention.